Плазмовий вміст тканинних біомаркерів при гіпертонічній хворобі - Волошина, Ірина Миколаївна (My University, 2011)
Резюме. Проведено определение плазменного содержания и взаимосвязь трансформирующего фактора роста- β1 (ТФР-β1), металлопротеиназы-9 (ММП-9) и тканевого ингибитора металлопротеиназ 1 типа (ТИМП-1) у 70 пациентов с гипертонической болезнью ІІ-ІІІ стадии. Для определения взаимосвязи между тканевыми биомаркерами, возрастом пациентов, уровнем АД и степенью поражения органов-мишеней (индексом массы миокарда левого желудочка, толщиной интимомедиального сегмента общих сонних артерй, наличием атером) был проведен корреляционный анализ. Установлено, что плазменное содержание тканевых биомаркеров значительно повышено у больных ГБ по сравнению с нормотензивными лицами. При ІІ стадии ГБ отмечено достоверное повышение уровней ТФР-β1 и ТИМП-1, между которыми существует прямая корреляционная взаимосвязь. При ІІI стадии ГБ у лиц, перенесших ишемический инсульт, в процессах ремоделирования сердца и сосудов наиболее активно участвует ММП-9 и ТФР-β1. Summary. The estimation of the plasma content and relationship of transforming growth factor-β1 (TGF-β1), metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinase type 1 (TIMP-1) in 70 patients with essential hypertension (EH) stage II-III was done. Cross-correlation analysis was done with purpose to reveal the possible relationship between tissue biomarkers, age of patients, blood pressure and severity of target organdamaging (index of left ventricle mass myocardium, carotid intima-media thickness, presence of atheromas). It was established that the plasma content of tissue biomarkers was significantly increased in all hypertensive patients compared with normotensive individuals. In hypertensive patients without stroke the levels of TGF-β1 and TIMP-1 were significantly higher than in control group and a direct correlation between these biomarkers was observed. In hypertensive patients who had ischemic stroke in anamnesis in the process of heart and vessels remodeling MMP-9 and TGF-β1 are involved the most actively
Keywords: гіпертонічна хвороба; трансформуючий фактор росту-β1; металопротеіназа-9; тканинний інгібітор металопротеіназ 1 типу; hypertension; transforming growth factor-β1; metalloproteinase-9; tissue inhibitor of metalloproteinases type 1